2002
DOI: 10.1016/s0022-5347(05)65108-7
|View full text |Cite
|
Sign up to set email alerts
|

Training Postgraduate Urologists in Laparoscopic Surgery: The Current Challenge

Abstract: This mini-fellowship model provides practicing urologists with a clinically applicable teaching experience to learn a new surgical concept using a familiar training pattern. It may be a more rapid and safe process of disseminating laparoscopic urological surgery to community urologists. Based on this model it would be possible for centers of excellence in each state to establish similar training programs for the corresponding urological community, thereby, bringing the teaching of new surgical skills to a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 2 publications
0
33
0
2
Order By: Relevance
“…40,43 In view of these barriers, several mentored and simulator-based training programs consequently emerged to facilitate skill transfer from experienced to laparoscopy-naive urologists. [44][45][46] The high percentage of provider-attributable variance also may reflect unmeasured differences in practice setting (and consequent access to information) among surgeons in our sample. That is, most providers make conclusive decisions about innovations based on interactions with local peer adopters rather than on scientific research or mass-media channels.…”
Section: Discussionmentioning
confidence: 97%
“…40,43 In view of these barriers, several mentored and simulator-based training programs consequently emerged to facilitate skill transfer from experienced to laparoscopy-naive urologists. [44][45][46] The high percentage of provider-attributable variance also may reflect unmeasured differences in practice setting (and consequent access to information) among surgeons in our sample. That is, most providers make conclusive decisions about innovations based on interactions with local peer adopters rather than on scientific research or mass-media channels.…”
Section: Discussionmentioning
confidence: 97%
“…43 More vigorous training has been shown to expedite the learning process, transfer technical skill at a higher rate, and lead to higher retention over the longterm. 39,[44][45][46] To promote the advancement of patient care through new surgical technologies while also ensuring patient safety, the American College of Surgeons has established multiple Accredited Education Institutes to facilitate transfer of surgical innovation to practicing surgeons, [47][48][49] similar programs may be beneficial for urologists and other surgical oncologists who are faced with the challenge of adopting complex new technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Shalhav and colleagues (5) found that an intensive 1 : 1 mentor : trainee experience at the postgraduate level, while challenging to accomplish, did improve the likelihood of the training surgeon assimilating this surgical technique into his/her clinical practice. In their study, both the urologists entered into the programme went on to incorporate laparoscopy into their surgical practice immediately following the training programme.…”
Section: Discussionmentioning
confidence: 99%